Precipitação pluviométrica e interna em povoamentos de Eucalyptus spp. em Rosário do Sul, RS - Consensa, Catarine Barcellos (2012)
In hydrological studies for understanding the water balance on experimental watersheds, the importance of knowing the possible "initial rain losses' in the system by the rainfall interception of the vegetation canopies are emphasized. Thus, there is the interest on studying the thoughfall behavior in planted forest with Eucalyptus dunnii Maiden, to 6 years, with na average height of 19,0 m and Eucalyptus urograndis, to 5 years, with na average height of 22,1 m, because of its relevance on the balance of the hydrological processes in forested watershed with the genre in the municipality of Rosario do Sul / RS. The study aims to contribute on the thoughfall sampling in planted forest of Eucalyptus dunnii Maiden and Eucalyptus urograndis, implanted on characteristic Pampa biome area. This study was conducted during a hydrological year from April 2011 to May 2012. For the hydrologic monitoring were quantified the total precipitations, the thoughfall using 60 interceptometers in each plantation and the stemflow. To evaluate the variability of thoughfall, test was performed between the means of media for each catcher position (line, between line, canopy, and between canopy), hemispherical photographs were taken of the canopy above each catcher, and mapped the thoughfall. To analyze the number of collectors, drawings were performed on each 4 and 4 catchers until reach the 60 catchers sampled at field. The annual interception on the plantation of Eucalyptus dunnii was 10,0% of the total annual precipitated and 26,8% on the Eucalyptus urograndis plantation. The average thoughfall in the 'canopy' position had higher levels than the other positions, and showed significant differences regarding the other positions (line, between line, canopy, and between canopy) both for the throughfall in E. dunnii as for E. urograndis. and the 'canopy" showed 10% lower relative canopy openness among the positions of the Eucalyptus dunnii plantation with 29,89% (10% less than other positions) and on the Eucalyptus urograndis plantation the line and the canopy had lower value (19,0% e 20,96%). The relative canopy openness of the Eucalyptus dunnii plantation was higher than the canopy openness of the E. urograndis plantation, 37,37 % and 23,76% respectively. On the E. dunnii plantation, 24 or more catchers respond to the true mean when the criterion of 80% of the means are in the confidence interval of the true mean (60 catchers) and 32 catchers respond to the criterion of 90%. On the Eucalyptus urograndis plantation, 28 catchers respond when 80% of the mean are within the limits of the confidence interval, whereas for 90% to represent the average, the ideal number is of 32 catchers.